2022
DOI: 10.1111/all.15202
|View full text |Cite
|
Sign up to set email alerts
|

‘Too high, too low’: The complexities of using thresholds in isolation to inform precautionary allergen (‘may contain’) labels

Abstract: The disclosure of 'priority' allergens when present as an (intended) ingredient in foods is, in most countries, enshrined in legislation.However, the disclosure of unintended allergen presence (UAP) due to cross-contact or cross-contamination (e.g. through the use of shared production facilities) is not. 1 Many food businesses use precautionary allergen ('may contain') labels (PAL) to advise consumers as to the possibility of UAP; however, use of PAL is voluntary and not specifically regulated, and the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Subjective symptoms, although not necessarily indicating an actual reaction, 35,40 may be stressful. Naturally, it is of interest for the food industry not only to verify food safety but also a perception of safety for the customers 41 . In this study, there was no safe dose in terms of subjective symptoms as 27 patients reported subjective symptoms to doses ≤1 mg sesame protein.…”
Section: Discussionmentioning
confidence: 83%
“…Subjective symptoms, although not necessarily indicating an actual reaction, 35,40 may be stressful. Naturally, it is of interest for the food industry not only to verify food safety but also a perception of safety for the customers 41 . In this study, there was no safe dose in terms of subjective symptoms as 27 patients reported subjective symptoms to doses ≤1 mg sesame protein.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, studies reveal that the presence of PAL does not necessarily correlate with the actual presence or severity of UAP in products, further diminishing its reliability as a risk communication tool [15]. Analytical studies assessing UAP in food products underscore the variability in allergen concentrations, indicating that PAL alone may not accurately reflect the potential risk levels [16 ▪▪ ,17]. Additionally, products without PAL may still harbour UAP, challenging the assumption that absence of PAL implies safety [16 ▪▪ ].…”
Section: Precautionary Allergen Labellingmentioning
confidence: 99%
“…The final decision on an acceptable level of contamination in manufactured foods lies with the authorities, and therefore, the data presented here on Danish food allergic patients may facilitate the ongoing debate on how to improve allergen labeling and at the same time protect patients against allergic reactions. 37,38 There is not necessarily a parametric function which both gives a good fit to the total number of dose-responders and fits the lower part of the function (low dose respondents) as well. Several of the allergens had few observations in the low-doses regime and consequently had a large uncertainty in this part.…”
Section: 4mentioning
confidence: 99%